Monte Carlo simulation for offshore transportation. (1st January 2017) - Kim, Boram; Kim, Tae-wan
Abstract: Persistence analysis was conducted to determine the suitable timing for offshore operations, including transportation. Conventional persistence analysis determines the weather windows for special points: the start point, midpoint, and endpoint of the route. Such results are useful for operations with fixed points, such as loading and unloading at the start or endpoint. However, this approach has two limitations: a limited number of waypoints represent the total route, and the tow behavior under such weather conditions is not considered. This paper presents the development of a Monte Carlo simulation to determine the optimal timing for transporting an offshore structure. In this case, "optimal" means a low voyage duration for economical transportation and operational safety, such as the average towing tension between the tug and tow. A simulation was performed to determine the right time when the average towing tension and estimated time of arrival are low. The results of this study can contribute to safe and effective planning for offshore transport. Highlights: Simulation to determine the optimal timing for transporting an offshore structure. Voyage duration and towing tension are considered. The maximum difference for the voyage duration is 12.98 h (12.80%). The maximum difference for the average of towing tension is 246 kN (7.11%).